Avaliação do desempenho ambiental e energético da fase agrícola da produção de cachos frescos de dendê no estado do Pará - Martins, Thatyana Santiago (Universidade Federal do Tocantins, 2017)
With the leap in development arising from the industrial revolutions of the past century, the need for energy sources that met this development has increased dramatically; and the non-renewable source of resources responded to this indigence. However, with the oil crisis in the late 80s, governments realized the need for diversifying their energy matrix. In Brazil, the first biofuel production program of biomass as raw material emerged after the crisis, but with the recovery of the oil market the program was not strengthened. At the end of the last century, the environmental impact of the exploitation of fossil fuels became more evident; therefore, agreements between countries were signed in order to reduce GHG emissions. In 2003, through a decree, the National Program for Biodiesel Production, PNPB was created, and in 2005, Law n.° 11.097 made the addition of biofuel in diesel a mandatory thing. With the increasing demand of raw material for biofuel production, researches in order to assess the life cycle of production of the raw material were driven. Before this background, the aim of this study was to evaluate the environmental performance and energy production of fresh palm bunches in the state of Pará, referring to plantations in Malaysia, world's largest producer of palm oil. The methodology used was the Life Cycle Assessment, standardized by the ISO series 14 000. The most striking stage of production was the preparation of the area. In the categories of impact, climate change, eutrophication and acidification, brazilian plantation was less impressive. For energy balance, the state of Pará produced 5 power units less than Malaysia, yet still comparing the species with others already used as a feedstock for biofuels, the production of palm oil based on biodiesel is economically and environmentally feasible.